Multi-Disciplinary Engineering for Cyber-Physical Production Systems 2017
DOI: 10.1007/978-3-319-56345-9_13
|View full text |Cite
|
Sign up to set email alerts
|

Patterns for Self-Adaptation in Cyber-Physical Systems

Abstract: Engineering Cyber-Physical Systems (CPS) is challenging, as these systems have to handle uncertainty and change during operation. A typical approach to deal with uncertainty is enhancing the system with self-adaptation capabilities. However, realizing self-adaptation in CPS, and consequently also in Cyber-Physical Production Systems (CPPS) as a member of the CPS family, is particularly challenging due to the specific characteristics of these systems, including the seamless integration of computational and phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…However, design patterns for multi-agent systems are applied in several applications. Musil et al [30] propose new design patterns capturing best practices for self-adaptation in CPSs. Giese et al [31] describe several architectural patterns that describe reflection in self-aware computing systems.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…However, design patterns for multi-agent systems are applied in several applications. Musil et al [30] propose new design patterns capturing best practices for self-adaptation in CPSs. Giese et al [31] describe several architectural patterns that describe reflection in self-aware computing systems.…”
Section: Related Workmentioning
confidence: 99%
“…Content-based Routing aims at routing messages within a distributed monitoring setting according to the message's content. Ramirez specifies the design patterns by using structural UML diagrams and sequence diagrams.Musil et al propose three design patterns for selfadaptation, focusing on CPSs: Synthesize-Utilize, Synthesize-Command, and Collect-Organize[30]. Precisely, these multiadaptation patterns capture information on the used adaptation mechanism, the interactions between those mechanisms across layers, and a definition of layers (i.e., physical, proxy, communication, service middleware, application, and social layer).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The current surveys and systematic reviews mostly target CPS architectures (i.e., decomposition into smaller parts and their interconnection) and their applications, which is a well-known method to deal with the increasing complexity of those systems. This includes various aspects, such as Architectural Description Languages (ADL) [16] (called architectural languages (AL) in the paper) and self-adaptation [7], as well as many others [15] [12] [11]. For instance, in [17], the authors are interested in identifying the application domains, challenges, goals, and solutions of architecting CPSs.…”
Section: Introductionmentioning
confidence: 99%
“…The systematic study found links between challenges and the suggested solutions for architecting CPSs, which provided a clear idea as to what kind of research could be targeted in the future. In contrast to this, the researchers in [7] headed for finding out application domains and uncertainty types in self-adaptive CPS, and they were able to synthetize patterns from multiple adaptation mechanisms and identify on which layers of the CPS architecture they are applied. As a result of this study, the patterns present an engineering method to be used in designing future self-adaptive CPS.…”
Section: Introductionmentioning
confidence: 99%